Gender, Tenure Security and Landscape Governance. Synthesis of Studies from PIM’s Governance of Natural Resources Flagship Program, 2013-2020 - Kristjanson, Patricia M. (International Food Policy Research Institute, 2022)
A substantial body of research on these important issues comes from a research theme of the CGIAR Research Program on Policies, Institutions, and Markets (PIM) that focused on the governance of natural resources (Flagship 5, or PIM5). Research in Flagship 5 examined the policy and institutional foundations for improved natural resource management. It analyzed how tenure security affects sustain¬able management and how individuals, groups, and communities govern the land, water, fish stocks, and forests. An important focus of this work is on understanding who has what rights with respect to these resources, particularly women and members of marginalized groups; what their roles are in managing natural resources; and the livelihood benefits they receive. Without a contextualized understanding of these questions, policies and practices can inadver¬tently exclude women, reinforce historic practices of gender injustice, or introduce new inequalities that worsen natural resource management and poverty. Thus, research teams in Flagship 5 worked with partners in governments, universities, the private sector, and civil society with the goal of identifying actions that can strengthen the tenure rights of poor and marginalized people, particularly women, in order to improve the governance of natural resources; and that can strengthen institutional arrangements for sustainable use of natural resources within shared landscapes. This paper provides a synthesis of PIM5’s contributions to knowledge about gender and its influence on tenure security and landscape governance. The focus of Flagship 5’s research was on gender and social inclusion in relation to tenure (land and natural resources) and to landscape governance (for example, land use planning). This review focuses on a subset of the research studies undertaken in this program from 2013 to 2020. It discusses the scientific contributions to the broader wealth of related literature by analyzing and summarizing key lessons about gender from these studies, where possible, with respect to outcomes and impacts on natural resource management, food security, and poverty alleviation. This analysis will help researchers better communicate the results of the Flagship’s research in order to inform policymakers and donors and to influence strategies and interventions aimed at addressing challenges related to these three arenas.